Sweetpotato Action for Security and Health in Africa (SASHA) Phase 2: Continuing to make a difference in sub-Saharan Africa! - International Potato Center (2014)
In 2009, the Sweetpotato Action for Security and Health in Africa (SASHA) project set out to improve the food security and health of poor families in sub-Saharan Africa (SSA) by exploiting the untapped potential of sweetpotato. The project seeks to tackle the bottlenecks along the sweetpotato value chain that prevent the full exploitation of crop’s potential. The $22.5 million, five year Phase 1 effort (2009-2014) was led by the International Potato Center and implemented with over 30 partners, thanks to the support of the Bill & Melinda Gates Foundation.